Effets cicatrisants de quelques plantes médicinales Algériennes Etude expérimentale chez les rats - BENYOUCEF, NESRINE; GOUMIDI, INES (My University, 2024)
Wound healing is an extremely complex phenomenon, unique to each organism. It involves the processes of repairing a localized lesion and regenerating tissue. Wound-healing drugs include various galenic forms such as ointments, creams and gels. In addition to drugs, there are natural alternatives that can promote wound healing, such as medicinal plants: aloe vera, calendula and essential oils like lavender oil, tea tree oil or rose hip oil. In this study, the healing activity of sesame oil and linseed gel was investigated in Wistar rats following the provocation of burns and wounds. The study was carried out by administering creams by the cutaneous route every other day and monitoring the healing phenomenon by measuring the percentage of inhibition in the rats, which were monitored for 48 hours. All the rats were divided into two categories. In the burn model, the rats were divided into 4 groups. Lot 1 contained a single rat which was the negative control, lot 2 contained a single rat which was the positive control, lot 3 contained four rats which had received a natural treatment (sesame oil cream) and the last lot contained a single standard rat treated with Dexeryl (glycerol Vaseline kerosene). The percentage of contraction was calculated for the 4 groups and it was observed that the healing rate in the natural treatment group was 80%, in the STD treatment group 53% and in the T- group 69%. The results of the wound-healing power of flaxseed gel showed a 95% contraction rate in the PTn group, 50% in the STD group and 58% in the T- group. in the T- group. Wound-healing activity was assessed by estimating the reduction in burn and wound area, the time required for complete epithelialization and the resistance to skin breakdown. Analyses showed a difference in values between each batch and a different immunological response between rats from different batches. Histological studies of liver tissue and skin were carried out to determine the extent of collagen formation in burn-damaged tissue . Inflammation markers (CRP and Vs) were assayed, with the latter registering positive results. Results indicating the presence of inflammation and repaired tissue damage following the administration of natural sesame and flax seed treatments, which have apowerful scarring activity.
Keywords: burn; wound; healing power; rat; sesame seeds; linseeds